Analysis the Influence of 4C Skills in Improving Employability Skills and Learning Achievement of Vocational School - Nugroho, Eko; Wilonoyudho, Saratri; Budiwirawan, Agung; Nur, Muhammad; Putri, Aulia (CIVED, 2024)
Economic and technological advances in Indonesia require vocational school graduates to be able to work competently according to their fields. The Ministry of Education and Culture supports the 21st century learning model which refers to the 4C skills, namely Communication, Collaboration, Critical Thinking and Creative. Achievement in the learning process is used to measure the achievement of goals and the intelligence of students. To be able to enter and survive in the world of work, it is also necessary to prepare attitudes, character and skills in work or employability skills that start from the learning process. This study aims to analyze the influence of 4C skills in improving employability skills and learning outcomes. The approach used in this study is quantitative with the student population of the DPIB Expertise Program of SMK Negeri 3 Semarang. The sampling technique uses a total sampling of 72 respondents. This study uses multiple linear regression analysis techniques that have previously gone through analytical tests including (1) Normality Test, (2) Homogeneity Test, (3) Linearity Test. The results of the study showed that (1) there was an influence between learning achievement on 4C skills with a T value of 4.660, (2) there was an influence between employability skills on 4C skills with a T value of 9.520, and (3) there was a simultaneous effect between learning achievement and employability skills against 4C skills with an F value of 55.937. The simultaneous correlation of the three variables was 78.6% with a simultaneous influence value of 61.9%, the remaining value of 38.1% was influenced by other factors that were not studied by the researcher.